A System To Integrate And Manipulate Protein Database Using BioPerl And XML. - Zainol, Zurinahni; Salam, Rosalina Abdul; Abdullah, Rosni; Nur'Aini, Nur'Aini; Husain, Wahidah (ENFORMATIKA, 2005)

(untitled)
The size, complexity and number of databases used for protein information have caused bioinformatics to lag behind in adapting to the need to handle this distributed information. Integrating all the information from different databases into one database is a challenging problem.